DIFFERENCES IN INFLUENCE OF PINEAPPLE LEAF FIBER DIRECTIONAL ARRANGEMENT BY UNI-DIRECTIONAL AND BI-DIRECTIONAL ON IMPACT STRENGTH OF FRAR - Bella Sarita Fariandewi; Benni Benyamin; Budi Suhartono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: It is critical to treat tooth loss cases using dentures. Hot polymerized acrylic resin, is the most often used basis for dentures and is cured by applying heat. Heat cured acrylic base material has several disadvantages, it is fragile, easy to change color, porous, and easy to absorb liquids. The impact strength of acrylic-based dentures can increase by adding pineapple leaf fiber because the cellulose content in pineapple leaf fiber increases the bond's strength. The pineapple plant is a type of plant that is relatively inexpensive and easy to obtain. This study aims to analyze the effect of uni-directional and bi-directional fiber direction of pineapple leaf fiber on the impact of FRAR.Method: The method used in this study was a post-test-only control group design with a total sample of 30 pcs. Meanwhile, the measurement process of impact strength was done using the Universal Testing Machine and joules/mm was used as the unit of measurement. One Way Anova test was used as a statistical test and was followed by the Bonferroni Post Hoc test. Result: The results showed a significant effect of uni-directional fibers on the impact strength of FRAR. The uni-directional fibers group had the highest impact strength of the three groups, with an average of 0.024 J/mm2. Uni-directional fibers result in even pressure distribution, increasing the FRAR's impact strength. Conclusion: There is a difference in the effect of different arrangements of pineapple leaf uni-directionally and bi-directionally on the impact strength of FRAR